Gut dysbiosis promotes islet-autoimmunity by increasing T-cell attraction in islets via CXCL10 chemokine - Pöysti Sakari; Silojärvi Satu; Brodnicki Thomas C; Catterall Tara; Liu Xin; Mackin Leanne; Luster Andrew D; Kay Thomas WH; Christen Urs; Thomas Helen E; Hänninen Arno (United Kingdom, 2025)
CXCL10 is an IFNγ-inducible chemokine implicated in the pathogenesis of type 1 diabetes. T-cells attracted to pancreatic islets produce IFNγ, but it is unclear what attracts the first IFNγ -producing T-cells in islets. Gut dysbiosis following administration of pathobionts induced CXCL10 expression in pancreatic islets of healthy non-diabetes-prone (C57BL/6) mice and depended on TLR4-signaling, and in non-obese diabetic (NOD) mice, gut dysbiosis induced also CXCR3 chemokine receptor in IGRP-reactive islet-specific T-cells in pancreatic lymph node. In amounts typical to low-grade endotoxemia, bacterial lipopolysaccharide induced CXCL10 production in isolated islets of wild type and RAG1 or IFNG-receptor-deficient but not type-I-IFN-receptor-deficient NOD mice, dissociating lipopolysaccharide-induced CXCL10 production from T-cells and IFNγ. Although mostly myeloid-cell dependent, also β-cells showed activation of innate immune signaling pathways and Cxcl10 expression in response to lipopolysaccharide indicating their independent sensitivity to dysbiosis. Thus, CXCL10 induction in response to low levels of lipopolysaccharide may allow islet-specific T-cells imprinted in pancreatic lymph node to enter in healthy islets independently of IFN-g, and thus link gut dysbiosis to early islet-autoimmunity via dysbiosis-associated low-grade endotoxemia.